Analisis Sensivitas Lokal Model Penyebaran COVID-19 dengan Kelas Asymptomatic dan Symptomatic - Gautama, IPW; Tastrawati, Ni Ketut Tari (Jurnal Matematika; Vol 13 No 2 (2023), 2024)
Abstract : This study examines a mathematical model of the spread of COVID-19 by dividing the population into Asymptomatic and Symptomatic classes. This model considers various compartments such as susceptible individuals, affected by lockdown, exposed, symptomatic, asymptomatic, quarantined, and recovered. The Next Generation Matrix method determines the equilibrium point and basic reproduction number (R 0 ). A local sensitivity analysis is conducted to identify the parameters that most influence R 0 . The results show that the transmission parameter by symptomatic individuals (β I ) has the highest positive sensitivity, while the rate of movement out of the exposed and infectious classes (a and h) have the greatest negative sensitivity. These findings emphasize the importance of interventions such as rapid isolation and reducing infectious contacts to control the spread of COVID-19. Keywords : Sensitivity Analysis, COVID-19, Mathematical Model